An Analysis of the Social Role of Tourism Ambassadors in Bali Province - Alit Sankara (Bali Tourism Journal, 2025)
This study explores the 2022 Bali Tourism Ambassador program through the lens of Stuart Hall’s Theory of Cultural Representation to examine how identity, culture, and tourism are constructed and communicated in contemporary Bali. As tourism remains central to Bali’s economy, the involvement of youth through ambassador programs has become a strategic cultural initiative. Using a qualitative case study approach, data were collected via interviews, observations, and media analysis. Findings reveal that the Bali Tourism Ambassador contest functions not only as a promotional platform but also as a symbolic site for producing and reinforcing dominant narratives about the ideal Balinese youth—cultured, attractive, intelligent, and civically engaged. Through Hall’s reflective, intentional, and constructionist approaches, the study illustrates how cultural symbols, rituals, language, and performance converge to shape public perceptions of tourism, modernity, and local identity. Events such as quarantine, public speaking, and traditional attire are framed not merely as assessments but as ideological practices embedded in a “regime of representation.” While the program succeeds in cultivating youth as cultural agents and tourism promoters, its long-term impact depends on consistent institutional support, mentorship, and integration into broader tourism development agendas. Without post-event follow-up, many of the finalists’ innovative ideas risk remaining symbolic. This research contributes to understanding how youth-led initiatives can serve as mechanisms of cultural continuity, soft power, and developmental communication in tourism-centric societies.